Medical Image Processing Using MATLAB in Detecting Kidney Stones - Basiron, Muhammad Afiq; Mohamad, Mazita (Evolution in Electrical and Electronic Engineering, 2022)
IIn this research project, the primary aim is to propose a technique in image processing that will assist individuals, particularly doctors and radiologists in detecting kidney stones and resulting in excellent quality.  Several ultrasound images were acquired and then simulated in MATLAB software.  Pre-processing of the image was performed to produce better image quality before it is processed further. Then, the image was segmented and it was used to identify the region of interest in the image. During processing, it removes the unwanted information known as pixels from outside the region and the region of interest (ROI) model was used to discover an abnormal region.  Elimination of ‘unwanted pixel’ was done if the intensity value is 250 and below.  Based on the results, the proposed techniques have successfully detected the presence of kidney stones in the region of interest after the image is applied in the simulation.